2016
DOI: 10.1097/dcr.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Sphincter-Saving Procedures for Diffuse Crohn’s Disease of the Large Bowel

Abstract: Contemporary patients selected to have intentional IPAA for Crohn's colitis have disease characteristics very different from those selected to have ileorectal anastomosis. Long-term follow-up confirms intentional IPAA as an acceptable option in selected patients with Crohn's colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
10
0
3
Order By: Relevance
“…Only one study reported useful and comparable data on overall quality of life [26] using the Cleveland Global Quality of Life tool, 3 years after surgery. This study found that, in general, patients with IRA had lower quality of life scores than those who received proctocolectomy with ileoanal pouch but higher than those receiving a proctocolectomy with ileostomy.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported useful and comparable data on overall quality of life [26] using the Cleveland Global Quality of Life tool, 3 years after surgery. This study found that, in general, patients with IRA had lower quality of life scores than those who received proctocolectomy with ileoanal pouch but higher than those receiving a proctocolectomy with ileostomy.…”
Section: Resultsmentioning
confidence: 99%
“…En esta serie, la colectomía total con ileostomía fue la operación practicada con mayor frecuencia, porque tiene algunas ventajas que merecen ser destacadas: Permite extirpar el colon dañado sin dejar una anastomosis intraabdominal, lo que es particularmente importante en pacientes intervenidos de urgencia por una crisis grave o en aquellos que, aunque intervenidos electivamente, cursan con una forma crónica de la enfermedad y que al momento de la indicación quirúrgica presentan compromiso del estado nutritivo o simultáneamente están inmunocomprometidos por el uso de corticoides, inmunomoduladores o biológicos. Además, esta alternativa quirúrgica, al resecar todo el colon enfermo y preservar el recto, permite en la mayoría de los pacientes suspender el tratamiento inmunosupresor y dar lugar a que el paciente recupere su estado general para evaluar el recto y practicar una IRA 5,13 . Cuando la enfermedad respeta el recto y el paciente se encuentra en buenas condiciones nutricionales e inmunocompetente se plantea de entrada la IRA.…”
Section: Discussionunclassified
“…La experiencia acumulada con IRA en CC muestra cifras de reoperación por recidiva de hasta 30%. Sin embargo, es importante destacar que la IRA permite una adecuada función intestinal y una buena calidad de vida, por lo cual, si bien no se puede considerar como un tratamiento definitivo, estos 2 factores son suficientes para plantearla como una alternativa quirúrgica 5,9,13,21 . Además, la evaluación temprana en el postoperatorio de factores de riesgo de recurrencia, como son el tabaquismo, antecedente de fístula, enfermedad perianal o edad de inicio de la enfermedad, permiten considerar y justificar el uso profiláctico de antibióticos, inmunosupresores y eventualmente biológicos, con el fin de evitar o retardar la recurrencia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It was originally believed to affect only the small intestine, and was subsequently identified in the colon, too. This disease must be distinguished from ulcerohemorrhagic rectocolitis (another inflammatory idiopathic illness) with which it presents several similarities in respecct to the clinical, anatomopathological, radiological and evolutive characteristics (1).…”
Section: Introductionmentioning
confidence: 99%